Changes of Individuals at The Cultural Level Under the Influence of Social Processes in Uzbekistan - Lola Joniboevna Sokhibova; Jurakulov Jamol Komilovich (International Journal of Scientific Trends, 2025)
The article states that in the XXI century the process of formation of various professional and social knowledge, values, ideas has accelerated, and in this regard, it is necessary to determine the level of awareness of the individual. This problem can be solved only by studying the process of formation of the cultural level of the person because it is the cultural level that represents the level of awareness of the person of different knowledge, values and ideas. According to the authors, the cultural level is a concept that reflects the norm of a person’s awareness of national and universal values, the degree of mastery of knowledge and ideas accumulated by mankind over the centuries, the ability to act on the basis of these values and knowledge. It is constantly improving under the influence of economic needs, social situation, the current political regime, the activities of educational and cultural institutions in society. At the same time, there are social flaws that can negatively affect the character of a person’s cultural level. These defects include the devaluation of scientific knowledge, the emergence of immoral norms, ideological nihilism, the propagation of destructive ideas, the proliferation of pseudo-values and anti-values, the deformation of national traditions and ceremonies, the development of pseudo-literature and pseudo-art. In order to raise the cultural level of the individual in the context of the renewed Uzbekistan, first of all, it is necessary to analyze them in detail, determine the scope of impact and prepare a forecast of social consequences.